Factores culturales asociados que influyen en la conducta agresiva y pasiva de los estudiantes de la Institución Educativa de Chalán (2021)
Within the framework of coexistence, it is necessary for educational institutions at the national level to emerge with policies aimed at overcoming coexistence in the school, family and social environment that play an important role in the comprehensive training of students, which shape the context of the children and promote situations that cultivate reciprocal influences, precisely, the family is in charge of the first socialization and teaching positive behaviors that are the best way to strengthen values in infants. The objective of this research project is focused on identifying the associated cultural factors that influence the aggressive and passive behavior of fifth grade students from the educational institution of Chalán. The research that has been developed is descriptive, with a quantitative approach, with the post- positivist paradigm, it is a descriptive study, with a non-experimental design, two instruments were applied: a survey and an interview to the patients. students, parents and teachers of the educational institution of Chalán in order to collect information on coexistence in the different environments where children interact. The systematization allowed to show in more detail that the aggressive and passive behaviors of the students are a problem where various cultural factors influence where children are the main actors of school violence but at the same time they are victims of social violence because both the family, the school and society in general that have lead to negative examples that are used by infants to solve conflicts.